Presence and distribution of pepper viruses in Serbia - Petrović Dragana; Bulajić Aleksandra; Stanković Ivana; Ignjatov Maja; Vujaković Milka; Krstić Branka (Ratarstvo i Povrtarstvo, 2010)
Pepper is a very popular and profitable crop in Serbia and its production is growing rapidly as well as the importance of diseases caused by viruses. Virus infections interfere with development of pepper plants, reducing yield and fruit quality. More than 45 viruses have been isolated from pepper so far, and in our country the following are considered economically very important: Tobacco mosaic virus (TMV), Cucumber mosaic virus (CMV), Alfalfa mosaic virus (AMV), Tomato spotted wilt virus (TSWV) and Potato virus Y (PVY). During 2009, an investigation was conducted regarding the presence and distribution of pepper viruses in Serbia, which included a survey of different localities of transplant production, and both greenhouse and open field pepper crops. Collected samples were tested utilizing a double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) with polyclonal antisera specific for the detection of economically important pepper viruses: PVY, AMV, CMV, TSWV, TMV and Potato virus X (PVX). In the collected samples, presence of the four viruses (PVY, CMV, TSWV and AMV) was confirmed in single and mixed infections. In tested transplant samples, the most frequently detected virus was CMV (18.18%), while PVY was the most frequent in samples collected in greenhouse and open field pepper crops (32.56% and 51.21% respectively). The presence of TSWV was detected only in greenhouse-grown pepper crops, while the presence of PVX and TMV was not detected during this investigation. The obtained results indicated that PVY and CMV were widely distributed and the most frequent viruses in pepper crops in Serbia. Future investigation should include their detailed biological and molecular characterization, as well as the implementation of appropriate control measures in pepper productions.